Occurrence of Extended Spectrum Cephalosporin-, Carbapenem- and Colistin-Resistant Gram-Negative Bacteria in Fresh Vegetables, an Increasing Human Health Concern in Algeria - Widad Chelaghma; Lotfi Loucif; Esma Bendjama; Zineb Cherak; Mourad Bendahou; Jean-Marc Rolain (MDPI AG, 2022)
The aim of this study was to screen for extended spectrum cephalosporin-, carbapenem- and colistin-resistant Gram-negative bacteria in fresh vegetables in Batna, Algeria. A total of 400 samples of fresh vegetables were collected from different retail stores. Samples were immediately subjected to selective isolation, then the representative colonies were identified using matrix-assisted laser desorption ionisation time-of-flight mass spectrometry (MALDI-TOF-MS). Phenotypic and genotypic analyses were carried out in terms of species identification and relative antibiotic resistance. Transferability of the carbapenemase and mcr-bearing plasmids was verified by conjugation. The clonal relationships of carbapenemase and mcr-positive Escherichia coli isolates were studied by multi-locus sequence typing (MLST). Sixty-seven isolates were characterised and were mostly isolated from green leafy vegetables, where the dominant species identified included Citrobacter freundii, Klebsiella pneumoniae, Enterobacter cloacae, Stenotrophomona maltophilia, E. coli and Citrobacter braakii. PCR and sequencing results showed that E. coli was the bacterial species presenting the highest antibiotic resistance level in parallel to blaTEM (n = 16) and blaCTX-M-15 (n = 11), which were the most detected genes. Moreover, five isolates carried carbapenemase genes, including the blaOXA-48 and/or blaVIM-4 genes. The mcr-1 gene was detected in two E. coli isolates. MLST analysis revealed three different E. coli sequence types: ST101 (n = 1), ST216 (n = 1) and ST2298 (n = 1). Conjugation assays confirmed the transferability of the blaOXA-48 and mcr-1 genes. In this study we report, for the first time, the detection of the blaOXA-48 gene in E. coli and C. braakii isolates and the blaVIM-4 gene in vegetables. To the best of our knowledge, this is the first report on the detection of mcr-1 genes from vegetables in Algeria.